Clinical, Laboratory and Neuroimaging of Acquired Demyelinating Syndrome of the Children Admitted in a Tertiary Care Hospital in Bangladesh - Parvin, Jobaida; Saha, Dipa; Khan, Husnea Ara; Saha, Narayan Chandra; Hossain, Mohammad Monir (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Acquired demyelinating syndrome (ADS) are autoimmune inflammatory disorder affecting the white matter of brain, optic nerve and spinal cord, and it has long been unrecognized. Early diagnosis and proper management slow the disease progression and reduce mortality and morbidity. Objective: To find out the clinical, laboratory and neuroimaging patterns of ADS in children in Bangladesh. Materials and Methods: A cross-sectional study was conducted from July 2020 to January 2021 in the Department of Pediatric Neurology, National Institute of Neuroscience and Hospital, including 37 children <18 years who had acute neurological deficits and MRI evidence of demyelination. After enrollment detailed history, physical examination, CSF study, oligoclonal bands (OCBs), and anti-NMO antibody was done and managed accordingly. Statistical analysis was done using SPSS version 22. Result: The mean age was 8.79 ± 2.94 years, males were predominant. Most of the patients (24) had limb weakness (78.6%), headache (46.9%), altered consciousness (42.4%) and visual disturbance (39.4%). Monophasic ADEM (43%) followed by NMOSD (24%), TM (21%), ON (6%) and MS (6%) were common ADS. Common findings of brain imaging were bilateral (42.4%), multifocal (57.57%), juxtacortical (36.4%) and periventricular (24.2%) demyelinating lesions. Conclusion: This study concluded that pediatric ADS had diverse clinical and radiological presentations, which were difficult to recognize for substantial clinical overlap. J Bangladesh Coll Phys Surg 2025; 43: 134-138